2019
DOI: 10.29261/pakvetj/2019.076
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Chickens Affected with Tibial Dyschondroplasia by Application of Grape Seed Extract through Downregulating CA2 Gene and Enhancing Liver Functions

Abstract: Globally Tibial Dyschondroplasia (TD) is a serious metabolic syndrome in broilers that is identified by the accretion of the growth plate (GP) into the tibialmetaphyseal portion. Grape seed extract (GSE) is a well-known significant antioxidant since it possesses multifaceted anti-inflammatory, anti-cancer and reducing reactive oxygen ability. The experiment was intended to evaluate the proficiency of GSE to recover the chicks affected with TD. For this purpose, 210 chicks were bought and fed normal starter fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Carbonic anhydrase 2 (CA2) plays an important and pivotal role in various pathological pathways like bone resorption process in osteoblasts is initiated by CA2 (Borthwick et al, 2003). Higher mRNA expression of CA2 in TD chicks has been reported by Qamar et al (2019). Similar findings have been observed in our experiment regarding protein expressions of CA2.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Carbonic anhydrase 2 (CA2) plays an important and pivotal role in various pathological pathways like bone resorption process in osteoblasts is initiated by CA2 (Borthwick et al, 2003). Higher mRNA expression of CA2 in TD chicks has been reported by Qamar et al (2019). Similar findings have been observed in our experiment regarding protein expressions of CA2.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings have been observed in our experiment regarding protein expressions of CA2. This might be due to weakening of bones because of less deposition of minerals in TD chicks and CA2 initiated bone resorption to boost up the calcification process in cartilages (Qamar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This skeletal disease of chickens leads to failure in growth plate cartilage to become bone, which results in avascular cartilage and severe lameness in chickens . It is a frequently occurring leg abnormality and reported up to 30% in commercial broiler farms (Zhang et al, 2018b;Qamar et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress induces the release of Cyt-c from the mitochondria that is the key factor of apoptosis, while the antioxidant enzyme Gpx4 can eliminate lipid peroxides in the mitochondria to inhibit the production of Cyt-c and reduce apoptosis (73). DQ can also affect the caspase signal pathway by inducing oxidative stress to produce ROS and enhance the activities of caspase-3 and caspase-9 in the liver tissue (74)(75)(76)(77)(78). It is found that there is a relationship between Bax/Bcl-2 and caspase.…”
Section: Discussionmentioning
confidence: 99%